Legal Review of Muhammadiyah's Strategy in Preventing the Spread of Radicalism - Samsul Arifin; L.ya Esty Pratiwi; Asis Asis (Universitas Muhammadiyah Malang, 2024)
Radicalism among the youth is a serious challenge to security and social stability in Indonesia. Muhammadiyah, as one of the largest Islamic organizations in the country, plays a crucial role in preventing the spread of radicalism. This study aims to analyze Muhammadiyah's strategies in preventing radicalism among the youth, particularly through a legal and human rights (HAM) approach. This research employs a normative legal research method with a juridical and conceptual approach. Data is obtained through the study of documents and literature related to the radicalism prevention strategies implemented by Muhammadiyah. The findings indicate that Muhammadiyah's strategies in preventing radicalism focus on education, moderate preaching (dakwah), and character building of the youth based on the values of Islam as a blessing for all (rahmatan lil 'alamin). The legal and human rights approach is applied in the form of respect for freedom of religion, the right to education, and efforts to prevent discrimination as well as actions that violate the law in the process of preventing radicalism. However, there are challenges in implementing these strategies, particularly regarding the alignment between Muhammadiyah's programs and government regulations, as well as public perceptions of radicalism.